Transcriptomic Profiling Reveals Underlying Immunoregulation Mechanisms of Resistant Hypertension in Injection Drug Users - Jia J; Yang JQ; Du YR; Xu Y; Kong D; Zhang XL; Mao JH; Hu GF; Wang KH; Kuang YQ (Dove Medical Press, 2022)
Jie Jia,1,2 Ji-Qun Yang,3 Ying-Rong Du,3 Yu Xu,2 Deshenyue Kong,1,2 Xiu-Ling Zhang,3 Jun-Hong Mao,1,2 Gui-Fang Hu,3 Kun-Hua Wang,1,2,4 Yi-Qun Kuang1,2 1NHC Key Laboratory of Drug Addiction Medicine, First Affiliated Hospital of Kunming Medical University, Kunming Medical University, Kunming, 650032, People's Republic of China; 2Scientific Research Laboratory Center, First Affiliated Hospital of Kunming Medical University, Kunming, 650032, People's Republic of China; 3Third People's Hospital of Kunming City/Drug Rehabilitation Hospital of Kunming City, Kunming, 650041, People's Republic of China; 4School of Medicine, Yunnan University, Kunming, 650500, People's Republic of ChinaCorrespondence: Yi-Qun Kuang; Kun-Hua Wang, NHC Key Laboratory of Drug Addiction Medicine, First Affiliated Hospital of Kunming Medical University, Kunming Medical University, Kunming, 650032, People's Republic of China, Email yq610433@hotmail.com; wangkunhua1964@126.comBackground: Hypertension is a common complication in injection drug users (IDU), especially a high proportion of resistant hypertension occurs among them. However, the involving mechanisms remain largely unknown.Methods: We here investigated the key signaling moieties in resistant hypertension in drug users. Analyses were performed with high-throughput transcriptomic sequencing data of peripheral blood from individuals with drug-sensitive hypertension (Ctrl-DS), IDU with resistant hypertension (IDU-DR), and IDU with sensitive hypertension (IDU-DS).Results: We showed that 17 and 1 genes in IDU-DS, 48 and 4 genes in IDU-DR were upregulated and downregulated compared Ctrl-DS, and 2 and 4 genes were upregulated and downregulated in IDU-DR compared with IDU-DS, respectively (p ≤ 0.01 and |log2(FC)| ≥ 1). Differentially expressed genes (DEGs) between Ctrl-DS and IDU-DS were mainly involved in Gene ontology terms of immunoglobulin complex and blood microparticle. DEGs between IDU-DS and IDU-DR were mainly involved in immune system process and immunoglobulin complex. DEGs between Ctrl-DS and IDU-DR were mainly involved in immunoglobulin complex, blood microparticle and cytoplasmic vesicle lumen. We identified 2 gene clusters (brown modules, MEbrown; turquoise module, MEturquoise) correlated with IDU-DR and a gene cluster (magenta module, MEmagenta) correlated with IDU-DS by weighted gene co-expression network analysis (WGCNA). Functional analysis demonstrated that pathways of focal adhesion and focalin-1-rich granule lumen were involved in the development of IDU-DR, and the cytosolic large ribosomal subunit may relate to IDU-DR. Further, immune cell infiltration analysis demonstrated that the abundance of dendritic cells (DCs), natural Treg cells (nTreg), and exhausted T cells (Tex) in IDU-DR and IDU-DS, naïve CD8+ T cells in IDU-DS was significantly different compared with that in Ctrl-DS. The abundance of cytotoxic T cells (Tc) was significantly different between IDU-DS and IDU-DR.Conclusion: Our findings indicated a potential function of immunoregulation mechanisms for resistant hypertension.Keywords: drug use, hypertension, treatment-resistant, transcriptome, immunoregulation